Application of Foot Massage Therapy to Reduce Pain Scale of Old Age with Rheumatoid Arthritis in Perumnas Public Health Center Working Area Lubuklinggau City 2023 - Wibowo, Wahyu Dwi Ari; Martini, Sri; Yadi, Nadi April; Martalina, Wulan; Trisna, Efa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Arthritis in RA patients causes pain, swelling, and decreased joint range of motion. It can lead to decreased independence and limited activities, reducing the quality of life. The process of foot massage also impacts the process of vasodilation and increased blood circulation. It increases the activity of the autonomic nervous system, which stimulates increased production of endorphins, which is expected to reduce pain. The case study used a descriptive method with two old older adults with Rheumatoid Arthritis, using the family nursing care assessment and pain scale assessment. The application of foot messages is carried out for 20 minutes for three days. After applying foot massage for three consecutive days, the study showed a decrease in pain intensity between before and after the intervention was given to the two subjects. The subject's pain intensity decreased from moderate pain intensity to mild pain. Applying foot massage effectively reduces the intensity of Rheumatoid Arthritis pain.